AN SPEECH ACT USED BY ANNA AS THE SECOND CHARACTERS IN “ FROZEN” MOVIE SCRIPT - Neng Lina; Nadia Dahlia; Rasi Yugafiati (IKIP Siliwangi, 2019)
This research entitled An Analysis Speech Act Used By Anna As The One of Characters in “Frozen” Movie Script, in this analysis the writers to find out the utterances that appear and the influence for the hearer aster the utterances is stated. Each speech showing three parts of speech acts, namely locutionary, illocutionary, and perlocutionary. However, this study only focuses on the discussion of illocutionary acts because basically the aim of the research is to find out what illocutionary acts used by Anna as one of the characters in the frozen movie so that the sense of a speech can be understood well in certain social interaction. The film of Frozen was chosen as the source of the data in this research because of the many illocutionary acts of speech spoken by Anna. The data was collected from the “Frozen” movie script . Based on the result of the study, the data found there are five kinds of illocutionary acts in the script, namely; 102 representatives forces, 32 directives forces, 11 commisive forces, 41 expressives forces, and 1 declarative force.